Eighteenth Century and the Classics: An Account of Pope’s Windsor –Forest and Swift’s the Battle of the Books - Mohammed Ismail, Araz (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
Scholars agree that unlike the preceding Renaissance epoch and the ensuing Romantic period, both of which attempted to dissociate from a suffocating past, eighteenth century delighted in the past, considering it a patron rather than an adversary. An idea prevailed that appreciation of the classical past could assist in creating a more valuable, more rewarding future. The two big areas for consideration were the ancient Greek and Roman cultures and the writings of medieval age. Engagement with the past, however, was a two-edged sword; the past could be a prefect, wonderful model for imitation on the one hand, while on the other the decadence and the decline of the ancient civilizations could be a source of melancholy and apprehension. This paper investigates how Jonathan Swift and Alexander Pope engage with the past in their respective works The Battle of the Books and Windsor-Forest, in which they present their accounts of the debate that was popular during their time with regards to the success and prestige of ancient and modern authors. The first part of the article attends to the criticism levelled at the ways the two writers looked at and revered the ancients, in the context of eighteenth century revival of interest in the past. Then, it is illustrated that, while Pope is optimistic about the re-establishment of another Roman age, Swift does not hide his pessimism and disappointment about bringing back his beloved Ancients to life and practice.